1988
DOI: 10.1111/j.1469-8986.1988.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Third Ventricle Enlargement and Reduced Electrodermal Responsiveness

Abstract: Using a subsample of subjects from the Copenhagen schizophrenia high‐risk project, we investigated the relationship between enlargement of the third ventricle and phasic electrodermal activity, as measured by amplitude and frequency of responses to orienting, unconditioned, conditioned, and generalization stimuli. Subjects with enlarged third ventricles evidenced significant overall reductions in amplitude and frequency of response, and significantly lower response levels to orienting, conditioned, and general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…All seven of the schizophrenics with predominantly negative symptoms had suffered severe delivery complications and were ANS nonresponders. This supports the hypothesis that perinatal complications could be a causative factor in third ventricle enlargement, which may contribute to electrodermal hyporesponsiveness (Cannon et al, 1988), 241 and is also a typical computer tomographic abnormality in schizophrenics (Cannon, Mednick, & Parnas, 1989). Contrarily, in another subsample of 160 schizophrenics from the Copenhagen study, 6 of the 8 patients with predominantly positive symptoms had suffered severely instable environments for growing up and evidenced high levels of ANS responsiveness.…”
Section: Electrodermal Nonresponding In Schizophrenicssupporting
confidence: 75%
See 1 more Smart Citation
“…All seven of the schizophrenics with predominantly negative symptoms had suffered severe delivery complications and were ANS nonresponders. This supports the hypothesis that perinatal complications could be a causative factor in third ventricle enlargement, which may contribute to electrodermal hyporesponsiveness (Cannon et al, 1988), 241 and is also a typical computer tomographic abnormality in schizophrenics (Cannon, Mednick, & Parnas, 1989). Contrarily, in another subsample of 160 schizophrenics from the Copenhagen study, 6 of the 8 patients with predominantly positive symptoms had suffered severely instable environments for growing up and evidenced high levels of ANS responsiveness.…”
Section: Electrodermal Nonresponding In Schizophrenicssupporting
confidence: 75%
“…236 It could be further speculated that different EDA parameters are related to different pathogenetic factors Cannon et al (1988),. using a subsample from the Copenhagen study, found that individuals with enlarged third ventricles (which may point to hypothalamic and/or amygdalar deficits) showed significant overall reductions in EDR amp.…”
mentioning
confidence: 99%
“…It may also be due to disproportionate volume loss in localised, periventricular structures (Harrison, 1999). Disturbance of the autonomic nervous system (ANS) has been shown to be associated with negative symptom schizophrenia (Frith et al , 1979) and with widening of the third ventricle (Cannon et al , 1988). Widening of the third ventricle has been shown to be associated with negative symptoms (Andreasen et al , 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Cannon e.a. 32 vonden in een gemcngde groep van schizofrene patienten en 'high-risk'-proefpersonen (personen met een schizofrene mocder) dat 'non-responding* gepaard gaat met een vergrote derde ventrikel. De auteurs suggeren dat vergroting van het derde ventrikel een beschadiging van de anterieure hypothalamus impliceert aangezien de basis van deze vertrikel vvordt omringd door de anterieure hypothalamus.…”
Section: Discussieunclassified